Agro bacterium tumef aciens biovar 3 Responsible for Reduction in Yield and Vigour of Muscat d’ Alexandrie - Ferreira, J.H.S.; van Zyl, F.G.H.; Staphorst, J.L. (South African Journal of Enology and Viticulture, 2017)
Yield and vigour of crown gall (Agrobacterium tumefaciens) infected and healthy Muscat d’ Alexandrie vines were compared over a five-year period. Crown-gall-infected plants exhibited a significant reduction in vigour as indicated by shoot mass and trunk diameter. A significant reduction in yield occurred during two seasons only. Gall size on vines (percentage of trunk circumference covered by gall) varied from< 10% to 75%. The highest proportion of diseased plants in the trial (52%) had galls smaller than 10% while only a few plants (6%) had galls greater than 50%. The largest reduction in vigour and yield occurred in plants with galls> 50% of trunk circumference.